Reversal of Hartmann's procedure in patients following failed colorectal or coloanal anastomosis: an analysis of 45 consecutive cases. (9th October 2019) - Caille, C.; Collard, M.; Moszkowicz, D.; Prost à la Denise, J.; Maggiori, L.; Panis, Y.
Abstract: Aim: This study aimed to assess outcomes of Hartmann's reversal (HR) after failure of previous colorectal anastomosis (CRA) or coloanal anastomosis (CAA). Methods: All patients planned for HR from 1997 to 2018 following the failure of previous CRA or CAA were included. Results: From 1997 to 2018, 45 HRs were planned following failed CRA or CAA performed for rectal cancer ( n  = 19, 42%), diverticulitis ( n  = 16, 36%), colon cancer ( n  = 4, 9%), inflammatory bowel disease ( n  = 2, 4%) or other aetiologies ( n  = 4, 9%). In two (4%) patients, HR could not be performed. HR was performed in 43/45 (96%) patients with stapled CRA ( n  = 24, 53%), delayed handsewn CAA with colonic pull‐through ( n  = 11, 24%), standard handsewn CAA ( n  = 6, 14%) or stapled ileal pouch–anal anastomosis ( n  = 2, 4%). One (2%) patient died postoperatively. Overall postoperative morbidity rate was 44%, including 27% of patients with severe postoperative complication (Clavien–Dindo ≥ 3). After a mean follow‐up of 38 ± 30 months (range 1–109), 35/45 (78%) patients presented without stoma. Multivariate analysis identified a remnant rectal stump < 7.5 cm in length as the only independent risk factor for long‐term persistent stoma. Among stoma‐free patients, low anterior resection syndrome (LARS) score was ≤ 20 (normal) in 43%, between 21 and 29 (minor LARS) in 33% and ≥ 30 (major LARS) in 24% of the patients. Conclusion: HR can be recommended in patients following a failed CRA or CAA. It permits 78% of patients to be free of stoma. A short length of the remnant rectal stump is the only predictive factor of persistent stoma in these patients.